Clinical, pathological, and oncological outcomes in unclassified renal cell carcinoma compared to clear cell renal cell carcinoma - Guilherme Sawczyn; Caio Brambilla; Gilberto Jose Rodrigues; Maykon William Aparecido Pires Pereira; Leonardo Cardili; Paulo Afonso de Carvalho; Fabio Pescarmona Gallucci; Álvaro Sadek Sarkis; William Carlos Nahas; Mauricio Dener Cordeiro (Indian Journal of Urology)
Purpose: This study aims to assess the impact of unclassified renal cell carcinoma (uRCC) on clinical, pathological, and oncological outcomes compared with clear cell renal cell carcinoma (ccRCC). Materials and Methods: We analyzed the data of 48 uRCC and 688 ccRCC cases, collected from a histopathological database at a single center from July 2011 to August 2019. uRCC cases were confirmed according to the 2016 World Health Organization classification. Baseline characteristics, clinical findings, and oncological outcomes were compared between the groups. Results: Patients with uRCC exhibited the same clinical symptoms as ccRCC patients, a higher prevalence of lymphadenopathy (31.2% vs. 15.8%, P < 0.01), and greater sarcomatoid/rhabdoid differentiation on histology (12.5% vs. 5%, P = 0.03) compared to ccRCC patients. Although there was no difference regarding overall metastasis at initial diagnosis, distant lymphadenopathy (16.7% vs. 7.8%, P = 0.04) and liver metastasis (8.9% vs. 2.8%, P = 0.04) were more common in the uRCC group. The two groups had similar high-grade (HG) frequency on histology (62.5% for uRCC vs. 53.7% for ccRCC, P = 0.23). The estimated recurrence-free survival at 48 months was 94.3% for uRCC, 92.5% for low-grade (LG) ccRCC (P = 0.91), and 66.5% for HG ccRCC (P < 0.01). The estimated overall survival at 48 months was 66.1% for uRCC, 87.4% for LG ccRCC (P = 0.75), and 63.4% for HG ccRCC (P < 0.01). Conclusion: Our study demonstrates that uRCC has significantly higher rates of lymphadenopathy, sarcomatoid differentiation, and liver metastasis compared to ccRCC. Despite these differences, uRCC presents with similar clinical symptoms and histological grade as ccRCC. Furthermore, uRCC exhibits a recurrence rate comparable to LG ccRCC and an overall survival rate similar to HG ccRCC.